Multiplexed Molecular Imaging of Fresh Tissue Surfaces Enabled by Convection‐Enhanced Topical Staining with SERS‐Coded Nanoparticles. Issue 40 (29th August 2016) - Wang, Yu W.; Doerksen, Josh D.; Kang, Soyoung; Walsh, Daniel; Yang, Qian; Hong, Daniel; Liu, Jonathan T. C.
Abstract : There is a need for intraoperative imaging technologies to guide breast‐conserving surgeries and to reduce the high rates of re‐excision for patients in which residual tumor is found at the surgical margins during postoperative pathology analyses. Feasibility studies have shown that utilizing topically applied surface‐enhanced Raman scattering (SERS) nanoparticles (NPs), in conjunction with the ratiometric imaging of targeted versus untargeted NPs, enables the rapid visualization of multiple cell‐surface biomarkers of cancer that are overexpressed at the surfaces of freshly excised breast tissues. In order to reliably and rapidly perform multiplexed Raman‐encoded molecular imaging of large numbers of biomarkers (with five or more NP flavors), an enhanced staining method has been developed in which tissue surfaces are cyclically dipped into an NP‐staining solution and subjected to high‐frequency mechanical vibration. This dipping and mechanical vibration (DMV) method promotes the convection of the SERS NPs at fresh tissue surfaces, which accelerates their binding to their respective biomarker targets. By utilizing a custom‐developed device for automated DMV staining, this study demonstrates the ability to simultaneously image four cell‐surface biomarkers of cancer at the surfaces of fresh human breast tissues with a mixture of five flavors of SERS NPs (four targeted and one untargeted control) topically applied for 5 min and imaged at a spatial resolution of 0.5 mm and a raster‐scanned imaging rate of >5 cm 2 min −1 . Abstract : For Raman‐encoded molecular imaging of fresh tissues with a high degree of multiplexing, a convection‐enhanced topical staining method has been developed that improves the binding of surface‐enhanced Raman scattering coded nanoparticles to various cell‐surface receptors. A custom topical‐staining device/method enables the simultaneous imaging of four or more cancer biomarkers at the surfaces of fresh surgical specimens after only 5 min of staining.